Pengaruh Kualitas Aset, Likuiditas, Profitabilitas Terhadap Tingkat Kecukupan Modal Perbankan Yang Terdaftar di Bursa Efek Indonesia - Safitri, Qhory Yulia; Oknaryana, Oknaryana; Marna, Jean Elikal (Jurnal Salingka Nagari, 2024)
This study examines how asset quality, liquidity, and profit-generating capability influence capital adequacy in banks registered on the Indonesia Stock Exchange (IDX) during 2019-2023. The studied population encompasses publicly traded banking companies on the IDX during this period, with 36 companies selected as samples using purposive sampling methodology. The analysis relies on secondary data extracted from these banks' financial statements. The researchers employ panel data regression methods to analyze the data. The research findings reveal several key insights: First, asset quality shows a negative influence on capital adequacy, although its impact is not statistically significant. Second, liquidity demonstrates a significant positive effect. Third, profit-generating capability exhibits a positive but statistically insignificant influence. Furthermore, this study reveals that collectively, these three factors - asset quality, liquidity, and profitability - play crucial roles in shaping capital adequacy. These discoveries emphasize the importance of effective liquidity management in maintaining financial stability, while highlighting the indirect contributions of asset quality and profitability in affecting capital adequacy of banks within Indonesia's financial sector.